Students' Perceptions of Using the Storyboardthat Application in Enhancing Creativity in Narrative Writing - Diah Yovita Suryarini; Wahyun Bardianing Panggalih; Amiruddin Hadi Wibowo; Arba Navalova Budiono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The need for creativity in language learning has encouraged teachers to integrate digital tools into writing instruction. However, many students still experience difficulties in generating ideas and developing creativity through traditional writing methods. This study aimed to explore students’ perceptions of using the StoryboardThat application to support creativity in narrative writing. A descriptive qualitative research design was employed. The participants were 20 fourth-semester students of the English Education Study Program at Wijaya Kusuma University Surabaya. Data were collected through a 35-item questionnaire focusing on creativity, motivation, confidence, and writing performance, supported by interviews, classroom observation, and document analysis. The data were analyzed qualitatively to identify recurring themes and patterns. The findings revealed that students perceived StoryboardThat as an engaging and helpful tool that stimulated creative thinking, increased motivation, and made narrative writing more enjoyable. The visual features of the application assisted students in developing story ideas, organizing narratives, and expressing individual writing styles. However, only a limited number of students reported improvement in grammatical accuracy and sentence structure. These findings suggest that StoryboardThat is effective in supporting students’ creativity and motivation in narrative writing, although additional instructional support is required to enhance language accuracy.